Palliative intraarterial chemoradiotherapy as a method of choice in the treatment of unresectable oropharyngeal tumors: a clinical case - R. V. Lutovinin; V. N. Oshchepkov; Yu. A. Shubina; V. V. Kokareva (Опухоли головы и шеи)
Introduction. Surgery is frequently preferable to therapy as it yields longer overall and recurrence-free survival. But surgery of locally advanced tumors of the oral cavity can not always guarantee preservation of oral functions. In the EORTC 24971 and RTOG 90-03 trials, effectiveness of conventional radiotherapy was demonstrated. Addition of brachytherapy allowed to double recurrence-free and overall survival. Implementation of proton therapy increased treatment safety. However, high cost of modern technology for radiotherapy limits its accessibility. Intra-arterial chemotherapy is characterized by lower toxicity. Additionally, it allows to create a pool for the 1st cycle of systemic circulation directly in the tumor and neighboring tissues, and a significant portion of the drug enters the draining lymph node replicating lymphogenic metastasis.The objective was to present a clinical case of successful treatment of inoperable squamous-cell carcinoma of the oropharynx using intra-arterial chemoradiotherapy.Clinical case. A patient sought medical help at the multidisciplinary clinical medical center “Medical City” where combination treatment was chosen: a course of chemoradiation therapy using an original approach combining external beam 3D-conformal radiotherapy and intraarterial chemotherapy. According to control computed tomography data, dynamics was described as partial response: 30 % reduction in marker lesions. The patient did not have any complaints and evaluated their quality of life as high which corresponded to the testing results.Conclusion. We have demonstrated benefits of intra-arterial chemoradiation therapy: low toxicity allows patients to receive a full course of radiotherapy without breaks and achieve high functional results. Considering palliative status of the patient, we did not aim to increase recurrence-free period but the objective of ensuring satisfactory quality of life was achieved. New, more physiological regimens of intra-arterial infusion will improve pharmacokinetic profile of chemotherapeutic drugs and will allow to achieve positive results.